2010
DOI: 10.1016/s1684-1182(10)60022-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of a New Formulation of Leishmania Major Antigen in Balb/C and Conventional White Laboratory Mice

Abstract: The new antigen formulation was able to stimulate and expand the lymphoid constituents of spleen tissue. The SWP is where immune responses and antibodies are produced. Therefore, the effect of the antigen preparations on secondary immune responses, adaptive immunity, and antibody production is important in determining the susceptibility of mice to cutaneous Leishmaniasis and the induction of immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…In essence, induction or fortification of a satisfactory immune response against leishmania parasites requires a potent and harmless vaccine which could be used to immunized susceptible species. According to our present and previous experiments on Balb/C mice [20][21][22][23][24], the vaccine seem to be safe and effective; 100% viability was recorded in all groups vaccinated with different doses of antigen (100 µg/0.1 ml or 200 µg/0.1 ml) with BCG or alcoholic extract of T. polium and or both as adjuvant. The provisional vaccine induced satisfactory cytokine responses in such a way that are not only safe to the vaccinated animals (Balb/C mice), could protect vaccinated subjects against challenging with live leishmania parasite as shown previously [30,31].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In essence, induction or fortification of a satisfactory immune response against leishmania parasites requires a potent and harmless vaccine which could be used to immunized susceptible species. According to our present and previous experiments on Balb/C mice [20][21][22][23][24], the vaccine seem to be safe and effective; 100% viability was recorded in all groups vaccinated with different doses of antigen (100 µg/0.1 ml or 200 µg/0.1 ml) with BCG or alcoholic extract of T. polium and or both as adjuvant. The provisional vaccine induced satisfactory cytokine responses in such a way that are not only safe to the vaccinated animals (Balb/C mice), could protect vaccinated subjects against challenging with live leishmania parasite as shown previously [30,31].…”
Section: Discussionmentioning
confidence: 65%
“…For detailed procedures please refer to Latifynia and collaborations [20][21][22] [23,24,25]. In brief, Balb/C and traditional white laboratory mice (n=40) were obtained at three months old from the Pasture institute.…”
Section: Animal Modelmentioning
confidence: 99%
“…For details of the procedure, please refer to the previous studies by Latifynia et al [21][22][23][24][25][26]. In time, the harvested parasites were diluted to a concentration of 5.92 × 10 10 parasites per milliliter.…”
Section: Culture and Isolation Of Leishmania Parasitesmentioning
confidence: 99%
“…IL-10 appears to constitute a major regulatory control in the outcome of infection, as well as the failure to produce IL-12 associated with the active form of the disease [20]. Our previous findings on the same newly formulated vaccine in two groups of mice (susceptible/Balb/c) and (resistance/ conventional) showed that it produced positive DTH [21] and led to an increase in white pulp size [22], which was statistically significant and correlated with effective immune responses, and was dependent on antigen doses, types of adjuvants, and injection groups [23]. Also, in other studies, our new formulated provisional vaccine was fortified by using BCG and the alcoholic extract of the Teucrium polium plant as an adjuvant in Balb/c mice, and after that the vaccinated subjects were challenged with live promastigote that were harvested from the culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…Then the collected parasites reached the concentration of 5.92 × 10 ¹˚, and were divided into five equal volume tubes. They were ready to prepare antigen for vaccine preparation like before [7][8][9][10][11][12][13][14][15].…”
Section: Culture and Isolation Of Leismania Parasitesmentioning
confidence: 99%